2013
DOI: 10.1002/alr.21220
|View full text |Cite
|
Sign up to set email alerts
|

The impact of culturable bacterial community on histopathology in chronic rhinosinusitis

Abstract: The culturable bacterial community has little impact on histopathology in CRS. While more sensitive tests may detect bacteria in the sinuses, the impact of the simple "culturable" bacteria on the underlying pathologic process is limited. Changes, such as subepithelial fibrosis, suggest colonization may lead to undesirable local mucosal damage and remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 11 publications
(12 reference statements)
1
14
2
Order By: Relevance
“…(11) . Investigation into the impact of other hypothesised associations including bacterial culture on inflammatory subtype was not demonstrated on a similar cohort of patients in a prior study (13) , whereas the effect genotype of bacterial growth was in this investigation.…”
Section: Non-taster (Avi/avi) P Valuecontrasting
confidence: 58%
See 1 more Smart Citation
“…(11) . Investigation into the impact of other hypothesised associations including bacterial culture on inflammatory subtype was not demonstrated on a similar cohort of patients in a prior study (13) , whereas the effect genotype of bacterial growth was in this investigation.…”
Section: Non-taster (Avi/avi) P Valuecontrasting
confidence: 58%
“…A meta-analysis conducted by Thanasumpun et al reported a culture rate of 63.7% in CRS patients, while 47% of CRS patients from a similar cohort cultured a pathogen (13,18) . Furthermore, the cultured bacteria in this study did not represent an acute or invasive infection in any cases and thus deemed colonised rather than infected by the investigators.…”
Section: Non-taster (Avi/avi) P Valuementioning
confidence: 99%
“…Accordingly, our literature review revealed that the different studies used a diversity of sampling methods (swabs, aspiration, molecular techniques) and sampling sites (middle meatus, maxillary sinus, other ethmoidal bulla, and frontal sinus), but none identified a distinct pattern of bacterial growth or a specific culprit species. The results of the most recent publications are summarized in table 1 [11,12,13,14,15,27,28,29]. …”
Section: Discussionmentioning
confidence: 99%
“…In general, a culturable pathogen in tissue samples was a good predictor of subepithelial fibrosis, Gram-negative bacteria having the strongest association. No significant associations have been established with other clinical outcomes [37].…”
Section: Metalloproteinasesmentioning
confidence: 96%